2011
DOI: 10.1016/j.jcin.2010.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Function After Paclitaxel-Coated Balloon Post-Dilation in Porcine Coronary Stent Model

Abstract: Post-dilation of bare-metal stents with PCB was associated with impaired vasodilatory response to Ach distal to the treated segments. Vasodilatory response after post-dilation with non-DCB was similar to control arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These results question the results of earlier trials indication a negative effect of DES on endothelial and microvascular function . Furthermore, we did not see an impaired vasodilatory response to acetylcholine distal to the treated segments, which has been reported in a porcine study by DCB . However, it has to be taken in account that most of these trials including our own suffer from modest sample sizes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results question the results of earlier trials indication a negative effect of DES on endothelial and microvascular function . Furthermore, we did not see an impaired vasodilatory response to acetylcholine distal to the treated segments, which has been reported in a porcine study by DCB . However, it has to be taken in account that most of these trials including our own suffer from modest sample sizes.…”
Section: Discussionmentioning
confidence: 87%
“…Different approaches of local intravascular drug delivery may influence endothelial and microvascular function. Preclinical reports show conflicting data on the influence of short time paclitaxel application on vasomotion and endothelial function . Therefore, the aim of this clinical trial was to study the influence of BMS mounted on a paclitaxel coated balloon (DCB + BMS) versus a BMS or a sirolimus‐eluting stent (DES) on coronary restenosis and endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation of no-reflow after DEB angioplasty is related to paclitaxel. A recent study of paclitaxel-coated balloons in a porcine model showed that the paclitaxel-coated balloon is associated with impaired vasodilatory responses to acetylcholine distal to the treated segments 7). The other possible explanation is related to the coating.…”
Section: Discussionmentioning
confidence: 99%
“…63 Two of the main strategies for local delivery from balloons have occurred via elution of drug solution from porous balloon catheters 6466 and drug-coated balloons. 62,67,68 Porous balloons are able to directly transfer drugs to the adjacent vessel wall using inflation pressure, which forces the solution from the balloon lumen to the tissue of the vessel wall; however, a delicate balance between sufficient pressure to deliver agents into the wall of the vessel, yet prevent mechanical wall damage must be achieved. 64,65,69,70 The use of drug-coated balloons presents another strategy for local delivery.…”
Section: Localized Therapeutic Delivery From Stent and Balloon Platformsmentioning
confidence: 99%